THE PRACTICE OF EVALUATING THE ECONOMIC EFFICIENCY OF THE INNOVATIVE PROJECT - I. A. Vorobiev; E. V. Omelchenko (Модернизация, инновация, развитие, 2015)
At the present stage of development of the society of scientific and technical activities is the most important factor in the intensification of production and the growth of its economic performance. It is therefore important now gets to determine the effectiveness of research and development activities, improving the measurement methods of economic evaluation of innovative projects and innovation. For informed decision-making requires a deep study and objective assessment of the real situation. This is due to changes in economic relations between the producers and consumers of scientific and technical products. Earlier in this activity involved only state scientific institution and the enterprise, then now they are gradually joining financial institutions, commercial and non-profit organizations. The adoption of innovative solutions should be preceded by thorough and comprehensive analysis of the economic feasibility of the innovative project. In this paper we propose to consider how business is costing innovative projects and determine their effectiveness for the enterprise business hotel.